Manual de egipcio medio - Zamacona, Carlos Gracia (Archaeopress Publishing Ltd, 2018)
This is a second revised and updated edition of Carlos Gracia Zamacona's 'Manual de Egipcio Medio' (Handbook of Middle Egyptian). The text is designed as a primer, written in Spanish, to learn Middle Egyptian (2000-1500 BC) and a guide to read hieroglyphs